ForeSight - Platform Approach for Enabling AI-based Services for Smart Living - Bauer, Jochen; Hoffmann, Hilko; Feld, Thomas; Runge, Mathias; Hinz, Oliver; Mayr, Andreas; Förster, Kristina; Teske, Franz; Schäfer, Franziska; Konrad, Christoph; Franke, Jörg (How AI Impacts Urban Living and Public Health, 2019)
In future, smart home and smart living applications will enrich daily life. These applications are aware of their context, use artificial intelligence (AI) and are therefore able to recognize common use cases reliably and adapt these use cases individually with the current user in mind. This paper describes a concept for such an AI-based platform. The presented platform approach considers different stakeholders, e.g. the housing industry, service providers and tenants.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Artificial intelligence; Ecosystem; Platform; Smart home; Smart living